PERCEPTION OF INSECURITY AND SUBJECTIVE WELL-BEING IN MEXICO. A QUALITATIVE APPROACH - Martínez-Martínez, Oscar A. (2021)
The objective was to analyze how the perception of insecurity affects subjective well-being in women and men. The study was qualitative and was conducted in urban areas of four states of Mexico. The results show that there are differences by sex in how they value insecurity in their neighborhood, in the case of women their main concern is the safety of their children and other relatives, therefore, they experience greater nervousness and restlessness, while men tend to minimize insecurity in the neighborhood and only worryabout material losses.